Pengaruh E-Modul berbasis Model Pembelajaran Guided Inquiry terhadap Keterampilan Berpikir Kritis pada Materi Usaha dan Energi - Ariq Nurmahmuddin; Nana Nana; Rahmat Rizal (Universitas Sultan Ageng Tirtayasa, 2023)
This research stems from using learning materials that still consist mainly of textbooks and occasionally printed modules, resulting in low levels of students' critical thinking skills. This study aims to investigate the influence of an e-module based on the guided inquiry learning model on students' critical thinking skills on the topic of work and energy. The research method is a quasi-experimental design with a pretest-posttest control group design. The population in this study comprises all tenth-grade science students at SMA Negeri 3 Kota Tasikmalaya, and the sample was selected using cluster random sampling technique, with Class X MIPA 7 as the experimental group and Class X MIPA 8 as the control group. The data analysis technique includes prerequisite testing, hypothesis testing, and N-Gain analysis. Based on the hypothesis test results using the t-test, it was found that , specifically, 3.75 > 1.67, leading to the rejection of . Therefore, it can be concluded that using an e-module based on the guided inquiry learning model influences students' critical thinking skills on work and energy. The improvement in students' critical thinking skills was assessed using the N-Gain test, which yielded an average N-Gain score of 0.41, indicating moderate improvement.